6x+3(x-10)=61-(x-1)

Simple and best practice solution for 6x+3(x-10)=61-(x-1) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 6x+3(x-10)=61-(x-1) equation:


Simplifying
6x + 3(x + -10) = 61 + -1(x + -1)

Reorder the terms:
6x + 3(-10 + x) = 61 + -1(x + -1)
6x + (-10 * 3 + x * 3) = 61 + -1(x + -1)
6x + (-30 + 3x) = 61 + -1(x + -1)

Reorder the terms:
-30 + 6x + 3x = 61 + -1(x + -1)

Combine like terms: 6x + 3x = 9x
-30 + 9x = 61 + -1(x + -1)

Reorder the terms:
-30 + 9x = 61 + -1(-1 + x)
-30 + 9x = 61 + (-1 * -1 + x * -1)
-30 + 9x = 61 + (1 + -1x)

Combine like terms: 61 + 1 = 62
-30 + 9x = 62 + -1x

Solving
-30 + 9x = 62 + -1x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add 'x' to each side of the equation.
-30 + 9x + x = 62 + -1x + x

Combine like terms: 9x + x = 10x
-30 + 10x = 62 + -1x + x

Combine like terms: -1x + x = 0
-30 + 10x = 62 + 0
-30 + 10x = 62

Add '30' to each side of the equation.
-30 + 30 + 10x = 62 + 30

Combine like terms: -30 + 30 = 0
0 + 10x = 62 + 30
10x = 62 + 30

Combine like terms: 62 + 30 = 92
10x = 92

Divide each side by '10'.
x = 9.2

Simplifying
x = 9.2

See similar equations:

| (x-2)*(x-3)*(x-4)*(x-5)=360 | | 7/9(0.8) | | 16+19+x=56 | | 4x5/12 | | (14+10i)+(-4-18i)=0 | | 287=7(1-6n) | | 5x-5=85 | | 1-9(4d-2)-6d= | | 2x+y=(-6) | | 6.20x+5.60=5.10x+4.20 | | 4x+2y=176 | | 2y+2z=16 | | 16+19+x=19 | | 4x-5=85 | | -5x-2x=8-4+2x+1 | | (25b-6)-6(4b+1)=-2 | | 4g(16+2g)=8g+12 | | 3x+1.4=2x+23 | | -2(9-7x)-2(x-1)=8x | | (5v+6)(5v-5)= | | 5(5x+7)=3(8x+6)-5 | | x-21=61 | | (2x+5)(6x-1)=90 | | 3/4x+1/3=3/4(x+8) | | 9x^2+16y^2+6x+8y=2 | | 18=0.6(x+10) | | 16=m-4 | | 4.20x+5.60=6.20x+5.10 | | 5x/6x-5y/6y | | sin^2x+2sinx-3= | | x+(x*0.095)=55.82 | | -2(3x-8)+10= |

Equations solver categories